Maximum inhibitory dilution of mouthwashes containing chlorhexidine and polyhexamethylene biguanide against salivary Staphylococcus aureus - Nascimento, Andresa Piacezzi; Tanomaru, Juliane Maria Guerreiro [UNESP]; Matoba Jr., Fumio; Watanabe, Evandro; Tanomaru-Filho, Mario [UNESP]; Ito, Izabel Yoko (FapUNIFESP (SciELO), 2008)
Objective: The aim of the present study was to determine the in vitro maximum inhibitory dilution (MID) of two chlorhexidine-based oral mouthwashes (CHX): Noplak®, Periogard®, and one polyhexamethylene biguanide-based mouthwash (PHMB): Sanifill Premium® against 28 field Staphylococcus aureus strains using the agar dilution method. Materials and Methods: For each product, decimal dilutions ranging from 1/10 to 1/655,360 were prepared in distilled water and added to Mueller Hinton Agar culture medium. After homogenization, the culture medium was poured onto Petri dishes. Strains were inoculated using a Steers multipoint inoculator and dishes were incubated at 37°C for 24hours. For reading, MID was considered as the maximum dilution of the mouthwash still capable of inhibiting microbial growth. Results: Sanifill Premium® inhibited the growth of all strains at 1/40 dilution and of 1 strain at 1/80 dilution. Noplak® inhibited the growth of 23 strains at 1/640 dilution and of all 28 strains at 1/320 dilution. Periogard® showed inhibited growth of 7 strains at 1/640 dilution and of all 28 strains at 1/320 dilution. Data were submitted to Kruskal-Wallis statistical test, showing significant differences between the mouthwashes evaluated (p<0.05). No significant difference was found between Noplak® and Periogard® p>0.05). Sanifill Premium® was the least effective (p<0.05). Conclusion: It was concluded that CHX-based mouthwashes present better antimicrobial activity against S. Aureus than the PHMB-based mouthwash.
Keywords: Anti-infective agents; Bacteria; Chlorhexidine